The hospital anxiety and depression scale, in patients with multiple sclerosis - Pais-Ribeiro, J. (2020)
Purpose: Multiple sclerosis (MS) is a long-lasting disabling disease with psychological implications. Hospital Anxiety and Depression Scale (HADS) is a questionnaire developed to screen anxiety and depression among patients in hospital settings. The objective of this report was to study the metric properties of the Portuguese version of HADS regarding MS. Materials and methods: This was a cross-sectional study. Three hundred and eighty individuals with a diagnosis of MS, according to the revised McDonald criteria, were recruited from an outpatient Neuroimmunology Clinic of the city of Porto. Participants had a mean age of 40.04 years (SD =10.86), 63.9% of them were female. HADS consists of two subscales - anxiety and depression - scored separately, with seven items each. Results: The results of our study show the appropriateness of HADS for the identification of mood changes in people with MS and show good metric properties. Conclusion: It seems to be a useful tool for the scrutiny of mood disorders in Portuguese patients with MS. The questionnaire is also sensitive to disease when compared to people with other severe illnesses, and with people without the disease.